Engaging individuals living with dementia as stakeholders. Issue 1 (25th January 2023) - Moreno, Monica; Kline, Chelsea; Shubeck, Emily; Lanigan, Kerry; Fazio, Sam
Abstract: The Alzheimer's Association has been convening individuals living with dementia as stakeholders for nearly 2 decades. This article outlines the evolution of, and lessons learned from, the Association's leadership in stakeholder engagement. It will also highlight the contributions of the Association's Early Stage Advisory Group in the areas of public policy, programming and resources, medical and scientific advancements, and public awareness. In addition, this article will discuss the ways in which the research community has come to recognize the importance of including the voices of persons living with dementia in their work and has looked to the Association for guidance and leadership. Last, it will describe the future directions of the Association with regard to increasing the influence and profile of these key stakeholders.